2016
DOI: 10.1002/kin.21060
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of α‐Diketones: Kinetics of C5and C6Compounds with Cl Atoms and OH Radicals

Abstract: Carbonyls play an important role in atmospheric chemistry due to their formation in the photooxidation of biogenic and anthropogenic volatile organic compounds and their high atmospheric reactivity. The Cl-initiated kinetics of two α-diketones (2,3-pentanedione (PTD) and 2,3-hexanedione (HEX)) have been determined as well as the OH + HEX rate constant using atmospheric simulation chamber experiments and the relative rate method. Up to three different reference compounds were used to assess robust results. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Alcohol calibration curves (Figures S1−S6) were carefully determined through FTIR spectroscopy using a White cell with a 10 m optical length. 30 The formation of the OH radical through the ozonolysis of hexenols was reported by Atkinson et al 21 alcohol but would not affect the ozone decay in a significant manner at the high initial alcohol/ozone concentration ratios employed. The two experiments noted above were carried out to confirm the absence of an effect on the O 3 decay.…”
Section: ■ Experimental Sectionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alcohol calibration curves (Figures S1−S6) were carefully determined through FTIR spectroscopy using a White cell with a 10 m optical length. 30 The formation of the OH radical through the ozonolysis of hexenols was reported by Atkinson et al 21 alcohol but would not affect the ozone decay in a significant manner at the high initial alcohol/ozone concentration ratios employed. The two experiments noted above were carried out to confirm the absence of an effect on the O 3 decay.…”
Section: ■ Experimental Sectionmentioning
confidence: 81%
“…The ozone decay was monitored by a UV-absorption O 3 analyzer (Environment SA 42M) with a resolution time of 10 s. Preliminary tests showed that the investigated alcohols did not absorb at the wavelength of the ozone instrument (253.7 nm). Alcohol calibration curves (Figures S1–S6) were carefully determined through FTIR spectroscopy using a White cell with a 10 m optical length …”
Section: Methodsmentioning
confidence: 99%